An Exploration of The Relationship between Management Accounting and Economic Performance - Maurya, Dr.Shyam; Anand, Dr. Utkarsh (International Journal of Accounting and Economics Studies, 2025)
Globalization and technological advancements have made firms more vulnerable in the current corporate environment. As a result, a firm's ability to maintain a competitive edge over time is highly unclear. When determining competitive advantage, one of the most important elements is "cost."The shift in our economic landscape, along with its growth and development phases, is all part of what we now call the new normal. In this context, exploring how accounting ties into economic efficiency is crucial for boosting the competitiveness of businesses, enhancing the national economy, and fostering sustainable, healthy growth. The article starts by briefly discussing the link between accounting and economic benefits in this new normal. We believe that these insights can effectively contribute to the robust growth of social economics, as they highlight the dynamic relationship between accounting practices and economic advantages.
Keywords: Normal New; Accounting; Economic Benefits